1990
DOI: 10.1007/bf02411537
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial pattern of plastid gene expression during crucifer seedling development and embryogenesis

Abstract: Several genes which are located close together on mustard (Sinapis alba L.) chloroplast DNA have been found to differ in their temporal mode of expression throughout seedling development. One predominant expression program, exemplified by thepsbA gene, is characterized by an early (light-independent) rise in transcript levels, followed by subsequent further accumulation to levels which are much higher in the light than in darkness (development of 'competence' for photocontrol). Other genes located next to thep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
(42 reference statements)
2
5
0
Order By: Relevance
“…In several plant species a similar increase has been found for other nuclear-encoded photosynthesis genes (Walden and Leaver, 1981;Fiebig et al, 1990). Also in Arabidopsis the nuclear-encoded photosynthesis genes encoding the Chl n/b-binding proteins (CAB) and the small subunit of ribulose-l,5-bisphosphate carboxylase (RBCS) were transiently expressed during etiolated seedling development (Brusslan and Tobin, 1992).…”
Section: Activity Of the Pc Promoter In Etiolated Seedlingssupporting
confidence: 57%
“…In several plant species a similar increase has been found for other nuclear-encoded photosynthesis genes (Walden and Leaver, 1981;Fiebig et al, 1990). Also in Arabidopsis the nuclear-encoded photosynthesis genes encoding the Chl n/b-binding proteins (CAB) and the small subunit of ribulose-l,5-bisphosphate carboxylase (RBCS) were transiently expressed during etiolated seedling development (Brusslan and Tobin, 1992).…”
Section: Activity Of the Pc Promoter In Etiolated Seedlingssupporting
confidence: 57%
“…For example, activation of rbcS and cab gene expression in the first few days after germination and growth in total darkness has been observed in several dicot species (Walden and Leaver, 1981;Fiebig et al, 1990;Wanner and Gruissem, 1991;Brusslan and Tobin, 1992). In darkgrown monocots, similar developmental control has been observed for the rbcS and cab genes, but in these species leaf expansion proceeds at approximately the same rate in the light or dark (Dean and Leech, 1982;Mayfield and Taylor, 1984;Lamppa et al, 1985).…”
Section: Discussionmentioning
confidence: 83%
“…In maturing barley and wheat seedlings, accumulation of rbcS and cab mRNA was found to decrease with increased age of the seedling, but could be stimulated by subsequent illumination (Lamppa et al, 1985;Barkardottir et al, 1987;Rapp and Mullet, 1991). Developmentally controlled light-independent changes in chloroplast gene transcription have also been observed that occur temporally and spatially concomitant to changes in expression of nuclear genes for photosynthesis-related proteins (Deng and Gruissem, 1987;Baumgartner et al, 1989;Fiebig et al, 1990;Rapp and Mullet, 1991). These studies indicate that the initial expression of chloroplast genes and some nuclear genes encoding photosynthesis-related proteins is coordinated with leaf development and that this regulation is independent of light.…”
Section: Discussionmentioning
confidence: 99%
“…In these monocots, leaf-cell development proceeds to nearly the same extent in the dark as in the light (33 Transcription of plastid genes has also been observed to follow a similar developmental pattern. In the mustard Sinapsis alba, many plastid genes are transcribed in the dark, with trnK showing the same timing of increase and decrease as seen for cab in Arabidopsis (35). In barley, general plastid transcription reaches a peak in the same leaf sections that show peaks of rbcS and cab transcripts (32).…”
Section: Methodsmentioning
confidence: 95%